The Effect of Canva-Based Infographic Media on the Advertising Text Writing Skills of Grade VIII Students at SMP Negeri 2 Watulimo - Diah Ayu Saputri; Trinil Dwi Turistiani (Raja Zulkarnain Education Foundation, 2026)
Canva is an online graphic design application that can be used to create various types of designs such as infographics, a combination of information and graphics that can help readers understand information more easily. This study aims to describe: 1) the application of Canva-based infographic media in learning advertising text writing skills; 2) analyze the effect of using Canva-based infographic media on advertising text writing skills; 3) identify student responses regarding the application of Canva-based infographic media in learning advertising text writing skills. This study was conducted at SMP Negeri 2 Watulimo using a quantitative approach by implementing a quasi-experimental method through a pretest-posttest control group design. The research sample included 29 students in the experimental class and 26 students in the control class. Learning data were collected using observation guidelines and questionnaires while advertising text writing skills data were collected using test instruments (pretest and posttest). Learning data were analyzed thematically while advertising text writing skills data were analyzed using descriptive statistics. The results of the study showed that the average value of the experimental class increased from 67 to 81, while the value of the control class increased from 60 to 70. Thus, the use of Canva-based infographic media has a significant influence on advertising text writing skills.